The Development Approach of Wat Raikhing .in Samphran district, Nakhornprathom Province (PhraSunun Inung) - Inung, PhraSunun (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This purposes of this research were to: 1) study the development level of Wat Raikhing (Phra Aram Luang) in Sam Phran District, Nakhon Pathom Province; 2) compare the development level of Wat Raikhing (Phra Aram Luang); and 3) study the development approach of Wat Raikhing (Phra Aram Luang). The research sample consisted of 124 monks and people. The research instrument for data collection was a questionnaire constructed by the researchers. Data were analyzed with mean and standard deviation. The hypotheses were tested with t-test for two groups of variables and one-way ANOWA for three or more groups of variables. Pairwise comparison by least significant difference and the content analysis was also conducted. The finding of this research were as follows: 1. Overall, the development level of Wat Raikhing (Phra Aram Luang) was at a high level. When considering each aspect, all aspects were at a high level. The aspects with highest average were public facilities, followed by religious studies and religious propagation. The aspect with the lowest average was public welfare. 2. As for comparison of the development level of Wat Raikhing (Phra Aram Luang), overall gender, age, education level, and experiences in temple visiting made no difference. 3. The development approach of Wat Raikhing (Phra Aram Luang) were: 1) in administration aspect, the temple should be managed smoothly in an organized way; 2) in religious studies aspect, rules and regulation should be issued, teachers should be recruited and developed, students should be allocated, and supporting funds should be provided; 3) in religion propagation aspect, Buddhist sermon should be propagated to religious heirs and public in every way without any conflicts with Buddhist disciplines; 4) in public facility aspect, the buildings in a temple should have planned layout and Buddha history should be displayed in temple area as a study of Dhama; 5) in welfare education aspect, the temple should be arranged as a place for educating children and youths and provide education welfare; and 6) in public welfare aspect, the temple should be strengthen to be a part of society and monks should be trained to be spiritual supporters. Article history : Received 5 May 2018 Revised 7 August 2018 Accepted 16 August 2018 SIMILARITY INDEX = 5.09